A slow, continuous beam of cold benzonitrile. Issue 7 (21st February 2015) - Patterson, David; Doyle, John M.
<x xml:space="preserve">Abstract</x> A cold, continuous, high flux beam of benzonitrile has been created via buffer gas cooling.